2004
DOI: 10.1111/j.0014-3820.2004.tb01625.x
|View full text |Cite
|
Sign up to set email alerts
|

Relative Contribution of Dispersal and Natural Selection to the Maintenance of a Hybrid Zone in Littorina

Abstract: Abstract. Habitat preference behavior may play an important role in nonallopatric speciation. However, most examples of habitat preference contributing to differentiation within natural populations correspond to parasites or herbivores living in the discrete environments constituted by their animal or plant hosts. In the present study we investigated migration guided by habitat preference in the intertidal snail Littorina saxatilis in a hybrid zone associated with an ecotone across the shore, which is therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 57 publications
(59 reference statements)
0
31
0
Order By: Relevance
“…However Cruz et al (2004) considered that while migration guided by habitat choice was evident in this system, it played a minor role in the re-establishment of experimentally manipulated phenotypic gradients. They suggested that habitat choice may be in the process of evolving as a result of habitat-related fitness differences of different morphs.…”
Section: Adaptation Environment and Gene Flow 19mentioning
confidence: 98%
“…However Cruz et al (2004) considered that while migration guided by habitat choice was evident in this system, it played a minor role in the re-establishment of experimentally manipulated phenotypic gradients. They suggested that habitat choice may be in the process of evolving as a result of habitat-related fitness differences of different morphs.…”
Section: Adaptation Environment and Gene Flow 19mentioning
confidence: 98%
“…Experimental evidence for nonrandom dispersal in L. saxatilis ecotype populations has been obtained in both Spain and Sweden [78,82,83]. In the Swedish populations, displaced snails exhibited greater average dispersal distances than nondisplaced ones and dispersal differed between E and S ecotypes, in addition to a tendency to recapture snails in their own habitat more often than expected from random dispersal [83].…”
Section: Habitat Choice In Littorinamentioning
confidence: 98%
“…In avoiding the hazards of crab predation by their position on the shore (low in Spain, high in Britain and Sweden), these ecotypes are free to develop larger shell apertures, increasing foot area and thus grip on the substrate to minimise dislodgement. Nonrandom mating is also observed in each population of ecotype pairs [78][79][80][81], primarily due to assortative mating by size (see [72] for a review). L. saxatilis lacks a pelagic larval stage, instead exhibiting direct development where females retain their brood internally and release fully formed young [71].…”
Section: Habitat Choice In Littorinamentioning
confidence: 99%
See 1 more Smart Citation
“…Although we only discuss one here, there are several regional cases of this divergence, with ecotypes adapted to different microhabitats created by tidal and substrate variation. The best-studied ecotype pair has evolved at least three times independently in Galician Spain, where the two types specialize in and prefer either the high intertidal barnacle belt or the low intertidal mussel belt and occasionally hybridize in the intermediate area between those environments [134,135]. The main axes of morphological differentiation are in shell size and shape, which aid in resistance either to dislodging by wave action (thin, small shells with large apertures for the muscular foot) or to crab predation and desiccation stress (thick, large shells with small apertures), and there are additional differences in shell ornamentation [19].…”
Section: B4 Littorina Saxatilismentioning
confidence: 99%